Table of Content - - (Journal of Arabic Language Sciences and Literature, 2025)
Table of Content: 1. Verbal Antithesis in the Holy Quran: A Rhetorical, Statistical and Analytical Study Dr. Ahmed Mohammed Al-Farsi 2. Islam’s view of science Ms. Amani Saud Khaishan Al-Qurashi 3. The protagonist’s image in Palestinian novels after Oslo accords in light of critical discourse analysis: A reading of "when the volves grow old and velvet" Mr. Khalil Mahmoud Harb , Co-Prof. Musa Mitri Khoury 4. Functions of the Tropes in Jassim Al-Sahhih’s poetry Ms. Amani Ahmad Mohammad Alhajjaji 5. American Interconnected Text Theory: A Critical View of Western Reception Prof. Brahim Amri Mohamed 6. Manifestations of rhetorical condensation and its semantic impact in free poetry (Fadwa Touqan) as a model Poem (To the martyr Wael Zaatir) Dr. Abdullah Mohmmed Hommod Al-Tobi , Dr. Mahmood Saed Safe Al-Drmaki